Telaah Kritis Berbagai Risiko SDM Dalam Mempertahankan Kelangsungan Perusahaan - kuliman kuliman (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2020)
Human resource are very desicive resource for other resources and can be ascertained when human resources do not exist so there will be no componey moreover theris nothing to produce. Human resourcesare very unique and different from teh other resources. Accordingly to this way so all the company trought their management should give great attention so that what is the goal can be achieved. On the other hand in this achievment management in ofen faced with variousuncertain or is possibilities. On of the risks that must be a majorconcern is related to the risk of human resources. After reviewing, in this paper thera are a least seven tyoes of risk from human resources, namely, the risk of workplace accidents, teh risk of disability, illness, strikes, riots, death and dismissal. Furthemore, from the various risks, the management should be able to make good and right decisions in overcoming these various risks, so that good and appropriarte countermeasures, the company avoid the loss and sustainability of the company can be guarenteed in the future.